Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/ma11010120
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Starch Films with Natural Extracts: Physical, Chemical, Morphological and Thermal Properties

Abstract: The aim of this study is to analyze the properties of a series of polysaccharide composite films, such as apparent density, color, the presence of functional groups, morphology, and thermal stability, as well as the correlation between them and their antimicrobial and optical properties. Natural antioxidants such as anthocyanins (from cranberry; blueberry and pomegranate); betalains (from beetroot and pitaya); resveratrol (from grape); and thymol and carvacrol (from oregano) were added to the films. Few change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 45 publications
(53 reference statements)
3
41
0
Order By: Relevance
“…The latter behavior was also observed in the derivative curves (Figure 5B). Significant weight loss at the same range of temperatures was also reported by other authors for starch films prepared with natural extracts, as a consequence of the earlier thermal degradation of the extracts compared with that of starch …”
Section: Resultsmentioning
confidence: 98%
“…The latter behavior was also observed in the derivative curves (Figure 5B). Significant weight loss at the same range of temperatures was also reported by other authors for starch films prepared with natural extracts, as a consequence of the earlier thermal degradation of the extracts compared with that of starch …”
Section: Resultsmentioning
confidence: 98%
“…The monoterpenes account for about 90% of the EO and are endowed with a wide range of biological and pharmacological properties . Carvacrol and thymol are monoterpenes widely found in essential oils of the genus Origanum . These isomers of position (Figure ) have several antibacterial and antifungal activities and also anti‐inflammatory and analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Carvacrol and thymol are monoterpenes widely found in essential oils of the genus Origanum. [10] These isomers of position ( Figure 1) have several antibacterial and antifungal activities [11] and also anti-inflammatory [12] and analgesic [13] effects. These properties make these compounds strong candidates for the development of products for tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…However, this biopolymer has displayed certain limitations in the mechanical and antioxidant properties of its cast films . Studies of chitosan based material characterization have shown that the addition of polymers such as starch, gelatin and natural extracts have improved antioxidant and physicochemical properties . For example, blending biopolymers such as chitosan and collagen from jumbo squid byproducts produced films with enhanced mechanical properties due to an increase in the percentage of elongation and a decrease in the elastic modulus of the films, and these effects were related to the interactions between polymers …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Studies of chitosan based material characterization have shown that the addition of polymers such as starch, gelatin and natural extracts have improved antioxidant and physicochemical properties. 4,5 For example, blending biopolymers such as chitosan and collagen from jumbo squid byproducts produced films with enhanced mechanical properties due to an increase in the percentage of elongation and a decrease in the elastic modulus of the films, and these effects were related to the interactions between polymers. 2,6 One green technology that, in recent years, has been used for the improvement of the functional properties of proteins is high-intensity ultrasound.…”
Section: Introductionmentioning
confidence: 99%